Non-Negotiable Assets Accounting and Analysis of their Status - Bessonova, S.I. (Економічний вісник Донбасу, 2015)
In the article studied were the status of fixed assets in Ukraine. The problems of fixed assets, their modernization, repairs and depreciation. Recommendations were given with the objective of clarification of the classification of fixed assets, detailed accounting, control and analysis of non-current assets, as well as the results of the use of innovative products. У статті проведено дослідження стану основних засобів в Україні. Розглянуто питання обліку основних засобів, їх модернізації, ремонту та амортизації. Запропоновано рекомендації щодо уточнення класифікації основних засобів, деталізації обліку, контролю і аналізу стану необоротних активів, а також результатів використання інноваційної продукції. В статье проведены исследования состояния основных средств в Украине. Рассмотрены вопросы учета основных средств, их модернизации, ремонта и амортизации. Предложены рекомендации по уточнению классификации основных средств, детализации учета, контроля и анализа состояния необоротных активов, а также результатов использования инновационной продукции.